Encyclopedia of Life Sciences 2009
DOI: 10.1002/9780470015902.a0000573.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenesis Biochemistry

Abstract: Methanogenesis is the biological production of methane mediated by anaerobic microorganisms from the Archaea domain commonly called methanogens. The production of methane is the energy‐yielding metabolism of methanogens and is unique to these organisms. Methane is produced by three major pathways: (1) reduction of carbon dioxide, (2) fermentation of acetate and (3) dismutation of methanol or methylamines. All three pathways have in common the demethylation of methyl– coenzyme M to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Tetrahydromethanopterin (among other enzymes) catalyze the conversion of carbon dioxide to methane using hydrogen as an electron donor in hydrogenotrophic methanogens (Rouviere and Wolfe, 1988). Lessner (2009) reported H4MPT to be a structural analog to the enzyme tetrahydrosarcinapterin (H4SPT), which is involved in the shuttling of carbon from acetate's carboxyl group to methane by acetoclastic methanogens. Dimitru et al (2003) found that a competitive relationship between PABA and various PABA-like inhibitors for the active site on an enzyme (4-(b-d-ribofuranosyl)aminobenzene-5 0 -phosphate synthase) that catalyzes the first step in the biosynthesis of H4MPT.…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahydromethanopterin (among other enzymes) catalyze the conversion of carbon dioxide to methane using hydrogen as an electron donor in hydrogenotrophic methanogens (Rouviere and Wolfe, 1988). Lessner (2009) reported H4MPT to be a structural analog to the enzyme tetrahydrosarcinapterin (H4SPT), which is involved in the shuttling of carbon from acetate's carboxyl group to methane by acetoclastic methanogens. Dimitru et al (2003) found that a competitive relationship between PABA and various PABA-like inhibitors for the active site on an enzyme (4-(b-d-ribofuranosyl)aminobenzene-5 0 -phosphate synthase) that catalyzes the first step in the biosynthesis of H4MPT.…”
Section: Discussionmentioning
confidence: 99%
“…While they can be effective C sinks, wetlands are also the single largest natural source of atmospheric methane (~127−155 Tg annually) [5], a greenhouse gas with 25−35 times the global warming potential of CO 2 over a century timescale [6]. Methane production in wetlands is largely attributed to the activity of anaerobic archaeal methanogens [7]. Anaerobic archaea can produce methane via three pathways-by splitting acetate (acetoclastic methanogenesis), by reducing CO 2 using hydrogen as an electron donor (hydrogenotrophic methanogenesis), or by demethylating methyl-containing substrates such as methanol, methylamine, or dimethylsulfide (methylotrophic methanogenesis) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogenotrophic, methylotrophic, and acetoclastic pathways are the three major pathways for ruminal CH 4 production. The biochemical reactions and enzyme profiles involved in methanogenesis are well identified and described [37]. Methyl-coenzyme M reductase (mcr) is a key enzyme responsible for catalyzing the CH 4 -producing step in the process of methanogenesis.…”
Section: Effects Of Nitrocompounds On Methane Production and Related mentioning
confidence: 99%